CO₂-ի կլանումը դիամինների և ալկանոլ ամինների միջոցով - Սաքեյան, Անահիտ; Սաֆարյան, Էլյա; Հարությունյան, Արփինե («Ալվարդ Օհանջանյան Վառլենի»)
Coal, oil, and gas production emits billions of tons of carbon dioxide (CO₂) into the atmosphere every year. The effect of carbon dioxide on the atmosphere plays an essential role in the context of climate change and global warming. The planet Earth is on the verge of destruction due to the greenhouse effect. Rising CO₂ levels in the atmosphere pose a significant challenge with far-reaching impacts on the environment and society. The greenhouse effect is the process by which the temperature of the Earth’s surface increases due to greenhouse gases. Since the beginning of the industrial era in 1850, the countries with the highest carbon dioxide emissions have been the United States, followed by Russia and China. In the 2019 national greenhouse gas inventory of the Republic of Armenia, carbon dioxide emissions were the most significant, accounting for 55.7% of total emissions. In 2019, a deviation of +1.5°C from the average annual temperature of 1961-1990 was recorded. Thus, despite Armenia’s relatively small share (0.02%) of global anthropogenic greenhouse gas emissions, the country actively participates in international efforts to combat climate change. Ածխի, նավթի և գազի արդյունահանումը տարեկան միլիարդավոր տոննա ածխաթթու գազ (CO ) է արտանետում մթնոլորտ: Ածխաթթու գազի ազդեցությունը մթնոլորտի վրա կարևոր դեր է խաղում՝ կլիմայի փոփոխության և գլոբալ տաքացման համատեքստում։ Ջերմոցային էֆեկտի պատճառով Երկիր մոլորակը կանգնած է կործանման եզրին։ Ջերմոցային էֆեկտը այն գործընթացն է, որով Երկրի մակերևույթի ջերմաստիճանը բարձրանում է ջերմոցային գազերի պատճառով: 1850 թվականից, այսինքն՝ արդյունաբերական դարաշրջանի սկզբից ի վեր, ածխաթթու գազի ամենամեծ քանակությունը արտանետել են մի քանի երկիր երկրներ, որոնցից միշտ առաջատար է եղել ԱՄՆ-ը, որին հաջորդում է Ռուսաստանը, իսկ հետո՝ Չինաստանը: Հայաստանի Հանրապետության 2019 թ. ջերմոցային գազերի ազգային կադաստրում գերակշռում են ածխածնի երկօքսիդի արտանետումները, որի մասնաբաժինը ընդհանուր արտանետումներում կազմել է 55.7%: 2019 թվականին գրանցվել է +1.5°C շեղում 1961-1990 թվականների միջին տարեկան ջերմաստիճանից: Coal, oil, and gas production emits billions of tons of carbon dioxide (CO₂) into the atmosphere every year. The effect of carbon dioxide on the atmosphere plays an essential role in the context of climate change and global warming. The planet Earth is on the verge of destruction due to the greenhouse effect. Rising CO₂ levels in the atmosphere pose a significant challenge with far-reaching impacts on the environment and society. The greenhouse effect is the process by which the temperature of the Earth’s surface increases due to greenhouse gases. Since the beginning of the industrial era in 1850, the countries with the highest carbon dioxide emissions have been the United States, followed by Russia and China. In the 2019 national greenhouse gas inventory of the Republic of Armenia, carbon dioxide emissions were the most significant, accounting for 55.7% of total emissions. In 2019, a deviation of +1.5°C from the average annual temperature of 1961-1990 was recorded. Thus, despite Armenia’s relatively small share (0.02%) of global anthropogenic greenhouse gas emissions, the country actively participates in international efforts to combat climate change.
Keywords: Բնական գիտություններ